1987
DOI: 10.1085/jgp.90.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the ganglion cell response in the catfish and frog retinas.

Abstract: Responses were evoked from ganglion cells in catfish and frog retinas by a Gaussian modulation of the mean luminance. An algorithm was devised to decompose intraceUularly recorded responses into the slow and spike components and to extract the time of occurrence of a spike discharge. The dynamics of both signals were analyzed in terms of a series of first-through third-order kernels obtained by cross-correlating the slow (analog) or spike (discrete or point process) signals against the white-noise input. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…The third observation shows that there was cross-talk or interference between the center and surround; modulation of the center reduced the sensitivity of the surround. Here we recall that the kernel is a measure of incremental sensitivity (Sakuranaga et al, 1987). We found that the center's response was more robust than the surround's response; the center kernels were less prone to be influenced by the presence of annular modulation.…”
Section: Intracellular Responsesmentioning
confidence: 86%
See 4 more Smart Citations
“…The third observation shows that there was cross-talk or interference between the center and surround; modulation of the center reduced the sensitivity of the surround. Here we recall that the kernel is a measure of incremental sensitivity (Sakuranaga et al, 1987). We found that the center's response was more robust than the surround's response; the center kernels were less prone to be influenced by the presence of annular modulation.…”
Section: Intracellular Responsesmentioning
confidence: 86%
“…Ganglion cells were identified on the basis of their responses to a flash of light and some cells were morphologically identified by injection of dye. We have previously made several functional and morphological studies of catfish ganglion cells (Marmarelis and Naka, 1973;Naka and Can-away, 1975;Davis and Naka, 1980;Sakuranaga, Ando, and Naka, 1987;Naka, 1987a, 1988a, b). The data presented here are cross-referenced to those in our earlier studies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations